MiR‐148a promotes plasma cell differentiation and targets the germinal center transcription factors Mitf and Bach2. Issue 4 (12th March 2015) - Porstner, Martina; Winkelmann, Rebecca; Daum, Patrick; Schmid, Julia; Pracht, Katharina; Côrte‐Real, Joana; Schreiber, Sandra; Haftmann, Claudia; Brandl, Andreas; Mashreghi, Mir‐Farzin; Gelse, Kolja; Hauke, Manuela; et al.
<x xml:space="preserve">Abstract</x> B cells undergo affinity maturation and class switch recombination of their immunoglobulin receptors during a germinal center (GC) reaction, before they differentiate into long‐lived antibody‐secreting plasma cells (PCs). Transcription factors such as Bach2 and Mitf are essential during this process, as they delay premature differentiation of GC B cells by repressing Blimp‐1 and IRF4, two transcription factors required for terminal PC differentiation. Therefore, Bach2 and Mitf expression must be attenuated in activated B cells to allow terminal PC differentiation, but the precise mechanism remains enigmatic. Here, we provide evidence that miR‐148a, a small noncoding microRNA, fosters PC differentiation and survival. Next‐generation sequencing revealed that miR‐148a is the most abundant microRNA in primary human and murine PCs, and its expression is upregulated in activated murine B cells and coincides with Blimp‐1 synthesis. miR‐148a targets Bach2, Mitf and proapoptotic factors such as PTEN and Bim. When prematurely expressed, miR‐148a promotes the differentiation and survival of plasmablasts and reduces frequencies of IgG1+ cells in primary B‐cell cultures. In summary, we propose that miR‐148a is a new player in the regulatory network controlling terminal PC differentiation and could, therefore, be a therapeutic target for interfering with PC differentiation and survival.